ERP Implementation Project in a brewing manufacturer: the quality attribute as a performance differential - Nicoletti Junior, Alaercio; Martens, Mauro Luiz; Oliveira, Maria Célia de (Brazilian Journal of Operations & Production Management, 2018)
This article aims to discuss the importance of the focus on quality attributes in an ERP system implementation project in a Brazilian brewing industry. The quality, as part of the "iron triangle" for conducting projects, can be monitored and associated with the project performance from the indicators associated to the quality attributes. The case study covered an Enterprise Resources Planning (ERP) system implementation on 6 business units of a brewing manufacturer distributed in different regions of Brazil, followed for eighteen months and it involved interviews with stakeholders, analysis of routines and documents, and people observation. The success of the project could be attributed to the performance indicators by meeting the design assumptions and the perception of the teams and project managers.